2000
DOI: 10.1046/j.1365-2893.2000.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Health care, treatment patterns and cost of services for patients infected with chronic hepatitis C virus in a large insured New England population

Abstract: The purpose of this study was to describe the cost of health care and the patterns of treatment of young patients (under 65 years of age) identified in health insurance claims as having received services for chronic hepatitis C virus (HCV) infection. We screened computerized claims from a US indemnity and managed care organization for out-patient and in-patient diagnoses related to HCV. Treatment patterns and costs of services were evaluated in the following sites of care: in-patient care, emergency room, hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…While excess morbidity was higher in females and young age groups, the greatest burden was in middle-aged adults. Previous population-based linkage studies have examined risk of death from alcoholic liver disease and show a similar excess overall (standardized mortality ratios [8][9][10][11][12][13][14][15] [2,5] and a higher excess in females. The trends in our cohort are of concern, as high levels of alcohol intake are associated with an increased risk of fibrosis progression and liver cancer in people with chronic HCV infection [6,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While excess morbidity was higher in females and young age groups, the greatest burden was in middle-aged adults. Previous population-based linkage studies have examined risk of death from alcoholic liver disease and show a similar excess overall (standardized mortality ratios [8][9][10][11][12][13][14][15] [2,5] and a higher excess in females. The trends in our cohort are of concern, as high levels of alcohol intake are associated with an increased risk of fibrosis progression and liver cancer in people with chronic HCV infection [6,23].…”
Section: Discussionmentioning
confidence: 99%
“…HCV-associated hospital admissions have been described using population-based registers [9][10][11], and rates of hospitalization have been reported for specific HCV infected cohorts [12,13]. However, we know of only one other published study examining population-based hospitalization rates; in 469 HCV cases notified in Scotland [14].…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Medical inflation may explain some of this difference, but cost increases over time likely also reflect the HCV "age wave." Recent studies, recognizing this age-related trend in HCV disease severity and related costs, have projected short-and long-term HCV costs overall and have isolated costs driven by AdvLD.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…[16][17][18] However, in the most recently published economic analysis of HCV, which was based on a large database of medical and pharmacy claims from 2002-2006, Davis et al reported that the regression-estimated total PPPY all-cause cost paid by managed care plans was $20,961 for HCV patients compared with $5,451 for patients in a matched non-HCV cohort. 19 HCV-related costs accounted for $6,864 PPPY in the HCV cohort.…”
Section: R E S E a R C Hmentioning
confidence: 99%
“…The average total annual per capita costs for HCV patients was $10 925 compared to $1886 for all MarketScan patients. A cross-sectional analysis of a New England insurance plan found 191 patients with chronic HCV-related claims for a 3-year observational period at a cost of $39 384 per chronic HCV patient 27 . Managed care organizations need to have further information describing the costs and treatment of their patients with HCV.…”
Section: Hcv Costs Within a Managed Care Organizationmentioning
confidence: 99%